Factors Affecting Malaysian Millennials in Paying Debt - Suhaimi, Shadia; Nurul Huda Mohd, Siti; Hashim, Haniza; Baiti Shafee, Nur; Siew Sian, Yip (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to identify the causes that make Malaysian millennials or fresh graduates face difficulty in repaying their basic debts such as study loans, car loans or rental. Basically, debts can be viewed from different perspectives. It can be negative or positive, and it depends on the repayment pattern by the debtor itself. Therefore, as a smart millennial, they need to have good financial knowledge in managing their wealth so that they won’t face any problems in the future. It is because, when they failed to plan, then it means that they will easily fall into bankruptcy and face financial crisis in daily life. Hence, some questions arise on how fresh graduates manage their income in paying basic expenses such as electricity bills or rent. So, this study is focusing on investigating the factors that affect the ability of fresh Malaysian graduates in repaying debts. The questionnaire has been distributed and collected from 200 respondents, who are among fresh graduates, and this study tested the relationship between income, personal attitude, financial knowledge, heavy credit card spending, and high cost of living with the ability of fresh graduates to repay the debts.